Art at Home, School, University and in Public Life - Das, Jatin (JOURNAL OF INDIAN EDUCATION, 2025)
My generation imbibed the values of Gandhi’s thoughts. He impregnated the whole nation with the ideas of dedication, non violence and freedom of speech. With those fervours, while in schools, I joined Seva Dal and did volunteer work. I grew up in a traditional Hindu family and participated in innumerable festivals, puja and rituals, which inculcated in me, without my knowledge, with a sense of arts and aesthetics as a way of life. My home and the town I lived in had the basic components of various forms of art. Home as such is a sacred place. Art was not a separate entity; it was a way of life, embedded in every activity. While growing up, I painted, drew, swam, gardened, and never thought of art as a profession or career. I call my 50 years of work, I have done nothing but devote myself to my work and teach. My childhood Boy Scout temperament is still in me somewhere. Hence my indulgence and concern for art at home, in school, in the university and in public life. This is why and how I made the collection of artefacts, antiquities and handfans; to set up museums and collections for the future generations. I have served in different committees, both governmental and private, raising my voice, giving unsolicited advice for open-ended education, filled with arts and aesthetics, and art in public life. When you look at the interior landscape of Indian culture, there is a rich, holistic upbringing at home and in society. Our rich cultural heritage still survives, but it is unfortunately not linked to contemporary life. My concern is both at the micro and macro levels, beginning at home and extending to public life.